1983
DOI: 10.1212/wnl.33.6.766
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to lateral displacement of vision in patients with lesions of the central nervous system

Abstract: The visual-motor adaptation to lateral displacement of vision by prism glasses was studied in normal individuals and patients with cerebellar dysfunction, Parkinson's disease, right or left cerebral hemisphere lesions, Alzheimer's disease, or Korsakoff's syndrome. Adaptation was analyzed in two phases, the return to normal pointing with prism glasses in place (the "error reduction portion") and the mispointing in the opposite direction after the glasses were removed (the "negative aftereffect portion"). Negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
229
3
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(254 citation statements)
references
References 0 publications
18
229
3
4
Order By: Relevance
“…In accordance with literature (Deuschl et al 1996;Diedrichsen et al 2005;Gauthier et al 1979;Martin et al 1996;Maschke et al 2004;Tseng et al 2007;Weiner et al 1983), we found that patients adapted less well than controls. Also in accordance with previous work (Martin et al 1996;Maschke et al 2004;Weiner et al 1983), the deficit was not limited to the adaptation phase, but rather continued undiminished The third data column presents the outcome of group comparisons with t tests, and the last two columns are the correlations of patients' findings with ataxia scores and cerebellar volume. Symbols ***, **, and * indicate p \ 0.001, p \ 0.01, and p \ 0.05, respectively, and the absence of a symbol indicates p [ 0.05 Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with literature (Deuschl et al 1996;Diedrichsen et al 2005;Gauthier et al 1979;Martin et al 1996;Maschke et al 2004;Tseng et al 2007;Weiner et al 1983), we found that patients adapted less well than controls. Also in accordance with previous work (Martin et al 1996;Maschke et al 2004;Weiner et al 1983), the deficit was not limited to the adaptation phase, but rather continued undiminished The third data column presents the outcome of group comparisons with t tests, and the last two columns are the correlations of patients' findings with ataxia scores and cerebellar volume. Symbols ***, **, and * indicate p \ 0.001, p \ 0.01, and p \ 0.05, respectively, and the absence of a symbol indicates p [ 0.05 Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The cerebellum has also been implicated in a more complex form of motor learning, namely, sensorimotor adaptation to visual and mechanical distortions. This view is supported by clinical studies, which found that adaptation is often reduced or abolished in patients with cerebellar disease (Deuschl et al 1996;Diedrichsen et al 2005;Gauthier et al 1979;Martin et al 1996;Maschke et al 2004;Tseng et al 2007;Weiner et al 1983). Further support comes from functional neuroimaging studies, which observed an increase of cerebellar activity during an adaptation task (e.g., Flament et al 1996;Graydon et al 2005;Imamizu et al 2000;Krakauer et al 2004;Krebs et al 1998;Lang et al 1988).…”
Section: Introductionmentioning
confidence: 91%
“…is in receipt of a SERC studentship. The cerebellum has been implicated in the motor learning of hand-eye coordination tasks (Baizer & Glickstein, 1974;Weiner et al 1983). However, in a recent study (Cody et al 1992) we found no evidence that the inaccuracies of visuo-motor tracking shown by patients with cerebellar lesions resulted from deficits of learning or memory.…”
Section: Ipcontrasting
confidence: 61%
“…Pointing errors are thus usually assumed to disappear completely within a few trials. However, using a similar procedure of terminal error feedback, Weiner, Hallett, and Funkenstein (1983) noticed that a pointing bias of about 15% persisted after 25 pointing trials. Devane (1968) showed that the decrease of pointing errors over time during the recovery from wedge prism adaptation was also asymptotic.…”
mentioning
confidence: 99%